2017
DOI: 10.1021/acsami.7b11282
|View full text |Cite
|
Sign up to set email alerts
|

Design and Comparative Study of O3/P2 Hybrid Structures for Room Temperature Sodium-Ion Batteries

Abstract: Rechargeable sodium-ion batteries have drawn increasing attention as candidates for the post lithium-ion batteries in large-scale energy storage systems. Layered oxides are the most promising cathode materials and their pure phases (e.g., P2, O3) have been widely investigated. Here we report a series of cathode materials with O3/P2 hybrid phase for sodium-ion batteries, which possesses advantages of both P2 and O3 structures. The designed material, NaNiFeMnO, can deliver a capacity of 86 mAh g with great rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 39 publications
3
81
1
Order By: Relevance
“…These phase transitions and stacking faults result in an increased disorder and strain within the material as indicated by the increasing full width at half maximum (FWHM) of the ( 0 0 l ) reflections—especially at voltages around 4.2 V. However, the FWHM and intensity of these reflections are similar at OCV and at the end of discharge (2.5 V), suggesting very reversible phase transitions overall. These findings for P2/P3/O3‐Na x Mn 0.5 Ni 0.3 Fe 0.1 Mg 0.1 O 2 are in good agreement with the phase transitions reported previously for P2/O3‐type Na 0.78 Ni 0.2 Fe 0.38 Mn 0.42 O 2 , which has a very similar structural and chemical composition. Differently, the P2/O3‐type intergrowth Na 0.7 Li 0.3 Ni 0.5 Mn 0.5 O 2 , studied by Lee et al, showed less phase transitions, which is attributed to the incorporated lithium that prevents extensive structural changes upon electrochemical cycling.…”
Section: Resultssupporting
confidence: 92%
“…These phase transitions and stacking faults result in an increased disorder and strain within the material as indicated by the increasing full width at half maximum (FWHM) of the ( 0 0 l ) reflections—especially at voltages around 4.2 V. However, the FWHM and intensity of these reflections are similar at OCV and at the end of discharge (2.5 V), suggesting very reversible phase transitions overall. These findings for P2/P3/O3‐Na x Mn 0.5 Ni 0.3 Fe 0.1 Mg 0.1 O 2 are in good agreement with the phase transitions reported previously for P2/O3‐type Na 0.78 Ni 0.2 Fe 0.38 Mn 0.42 O 2 , which has a very similar structural and chemical composition. Differently, the P2/O3‐type intergrowth Na 0.7 Li 0.3 Ni 0.5 Mn 0.5 O 2 , studied by Lee et al, showed less phase transitions, which is attributed to the incorporated lithium that prevents extensive structural changes upon electrochemical cycling.…”
Section: Resultssupporting
confidence: 92%
“…The rate capacity is also increased, as the capacity at 1200 mA g −1 is raised from 15 to 65 mAh g −1 . A step further, Qi et al reported a series of P2–O3 Na x Ni 0.2 Fe x −0.4 Mn 1.2− x O 2 composites, and tuned the Fe/Mn ratio to balance the P2–O3 composition for optimal capacity, cyclic stability, and rate capability . In situ XRD analyses of the initial charge and discharge confirm reversible phase transformation of O3–P3–O3′ between 2.5 and 4.0 V (Figure d).…”
Section: Sibsmentioning
confidence: 91%
“…d) XRD patterns and corresponding crystal phases of Na x Ni 0.2 Fe x −0.4 Mn 1.2− x O 2 (NNFM) with various Na contents (0.7–1.0) and the resulting phase evolution; e) cyclic stability and f) rate capability of Na 0.78 Ni 0.2 Fe 0.38 Mn 0.42 O 2 (NNFM–0.78). Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Sibsmentioning
confidence: 99%
“…The electrochemical performance of this CSM shows the advantages of this material. Recently, another CSM of Na x Ni 0.2 Fe x −0.4 Mn 1.2− x O 2 (0.7 < x < 1.0) with a P2‐type and O3‐type hybrid structure was designed with different Na contents . The Rietveld refinement results and TEM images showed that the fraction of the P2‐type structure gradually decreased, while the fraction of the O3‐type structure increased (Figure b) as the Na content increased for the same heating process (950 °C).…”
Section: Structure Design and Adjustment Of Csmsmentioning
confidence: 99%